The close proximity of threat: altered distance perception in the anticipation of pain - Tabor, Abby; Catley, Mark J.; Gandevia, Simon C.; Thacker, Michael A.; Spence, Charles; Moseley, G. L. (Frontiers in Psychology, 2015)
Pain is an experience that powerfully influences the way we interact with our environment. What is less clear is the influence that pain has on the way we perceive our environment. We investigated the effect that the anticipation of experimental pain (THREAT) and its relief (RELIEF) has on the visual perception of space. 18 (11F) healthy volunteers estimated the distance to alternating THREAT and RELIEF stimuli that were placed within reachable space. The results determined that the estimated distance to the THREAT stimulus was significantly underestimated in comparison to the RELIEF stimulus. We conclude that pain-evoking stimuli are perceived as closer to the body than otherwise identical pain-relieving stimuli, an important consideration when applied to our decisions and behaviours in relation to the experience of pain.